The effectiveness of Evodia rutaecarpa hot compress on the recovery of gastrointestinal function after laparoscopic surgery for colorectal cancer: A propensity score-matched retrospective cohort study. - Miaoxin Huang; Junmiao Li; Wei Huang; Yuling Zhou; Lei Cai; Ming Liu (PLoS ONE)
Background Although the use of hot compresses with the herbal medicine Evodia rutaecarpa (ER) as a complementary and alternative therapy to promote recovery of postoperative gastrointestinal function is gradually increasing in clinical practice, there is still a lack of relevant empirical studies. Particularly, the role of ER hot compress therapy on gastrointestinal recovery post-laparoscopic surgery for colorectal cancer has not been well investigated. The purpose of this study is to evaluate the efficacy and applicability of ER hot compress therapy for the recovery of postoperative gastrointestinal function. Methods This is a retrospective cohort study. Patients were divided into two cohorts, the ER group and the non-ER group. Propensity score matching(PSM) was introduced to limit confounding, and independent samples t-tests, non-parametric tests, or Chi-squared tests were used to compare these two cohorts. Results A total of 454 patients were included, with 267 (59%) receiving ER hot compress therapy and 187 (41%) not. After 1:1 PSM, 320 patients were analyzed (160 in each group). Compared to the ER group, patients in the non-ER group had shorter times to return to a semi-liquid diet (p = 0.030) and hospital stay (p<0.001), as well as lower hospital costs (p<0.001). Subgroup analyses revealed no statistically significant differences in the length of hospital stay, hospital costs, postoperative time to return to full-liquid diet, or time to return to semi-liquid diet among stage I and II tumor patients. However, except for hospital costs, the means and standard deviations of the other indicators were generally lower in the ER group. Complication incidence showed no significant difference between the two cohorts before and after PSM. Conclusions The use of ER hot packs after laparoscopic surgery in patients with colorectal cancer has a non-significant effect on the recovery of the gastrointestinal function and, given the results of the study, it is likely that patients with early-stage tumors may benefit more. Therefore, healthcare providers need to consider the individualization, practicality, and economics of treatment options.